Strategic Leadership Models for Enhancing Supervisory Performance: A Phenomenological Inquiry at School Y Palembang, Indonesia - Sri Yusriani; Endi Rekarti; Said Ridho Abdillah; Bendaoud Nadif; Muji Gunarto (Siber Journal of Advanced Multidisciplinary, 2026)
This study examines how strategic leadership orientations and managerial decisions shape the performance of supervisory personnel in Islamic Senior High Schools in Palembang, Indonesia. Employing an Interpretative Phenomenological Analysis (IPA) approach (Smith et al., 2009) and grounded in qualitative inquiry principles (Creswell & Creswell, 2017), the research uncovers how supervisors interpret leadership expectations, negotiate structural constraints, and enact their roles in everyday practice. Data were generated through semi-structured interviews, field observations, and document review involving supervisory stakeholders at School Y. Findings reveal four key dynamics: (1) supervision planning is consistently initiated through early-year coordination, yet implementation fluctuates due to prioritization shifts and operational overload; (2) coaching occurs through school visitations and mentoring, but remains primarily administrative rather than pedagogical; (3) structural limitations, including inadequate competency-based recruitment, aging workforce profiles, and uneven professional development access, weaken supervisory agility; and (4) supervisors actively engage in adaptive meaning-making, self-learning, and informal peer collaboration to compensate for systemic constraints. The study concludes that effective supervisory development requires strengthened regulatory governance, sustained curriculum-based competency training, and strategic specialization of supervisory roles. Enhancing these mechanisms will enable supervisors to transition from compliance enforcers to instructional leaders capable of driving meaningful school improvement. The results contribute theoretically to supervisory governance within Islamic education and offer practical reform pathways for leadership-based supervision enhancement in Indonesian secondary schools.